Micro-ultrasound transperineal prostate biopsy as an alternative to MRI-US fusion transrectal biopsy - Black, Anna J.; Michalchuk, Quentin; Almarzouq, Ahmad; Gleave, Martin; Mannas, Miles P. (Canadian Urological Association Journal, 2025)
INTRODUCTION: ExactVu micro-ultrasound generates high-resolution images and promises to improve prostate biopsy performance, while transperineal prostate biopsy (TPB) has gained popularity due to its sterile technique. The aim of this study was to compare TPB using ExactVu to transrectal biopsy (TRB). METHODS: A retrospective analysis of patients who underwent TPB (n=306) using ExactVu or TRB (n=392) from 2019-2023 was performed. Clinical parameters were compared between the groups using Chi-squared test. Putative predictors of cancer on biopsy and upgrading on radical prostatectomy were investigated using logistic regression. RESULTS: More transperineal than transrectal biopsy patients had a Prostate Imaging- Reporting and Data System (PI-RADS) 5 lesion (40% vs. 28%, p=0.001) and were biopsynaive (53% vs. 39%, p<0.001). In patients with no previous diagnosis of prostate cancer, the clinically significant prostate cancer detection rate was higher in the TPB group (53% vs. 42%, p=0.01). Transperineal patients required fewer cores to obtain equal cancer detection rates (11±5 vs. 15±4 cores, p<0.01). Upgrading from grade group 1 to grade group ≥2 on radical prostatectomy was more common with TRB (9.1% vs. 2.1%, p=0.04). Urinary retention rate did not differ by biopsy type and two transrectal but no transperineal patients developed urosepsis. CONCLUSIONS: TPB required fewer cores to obtain a similar clinically significant prostate cancer detection rate when compared to TRB. TPB had fewer complications and a low upgrade rate. This suggests that cognitive fusion TPB using ExactVu is an excellent alternative to software fusion TRB.